Electron-hole asymmetry in the electron-phonon coupling in top-gated phosphorene transistor. (18th February 2016) - Chakraborty, Biswanath; Gupta, Satyendra Nath; Singh, Anjali; Kuiri, Manabendra; Kumar, Chandan; Muthu, D V S; Das, Anindya; Waghmare, U V; Sood, A K
Abstract: Using in situ Raman scattering from phosphorene channel in an electrochemically top-gated field effect transistor, we show that phonons with A g symmetry depend much more strongly on concentration of electrons than that of holes, wheras phonons with B g symmetry are insensitive to doping. With first-principles theoretical analysis, we show that the observed electon–hole asymmetry arises from the radically different constitution of its conduction and valence bands involving π and σ bonding states respectively, whose symmetry permits coupling with only the phonons that preserve the lattice symmetry. Thus, Raman spectroscopy is a non-invasive tool for measuring electron concentration in phosphorene-based nanoelectronic devices.